DETERMINATION OF TETRAFLUOROBORATE BY POTENTIOMETRIC TITRATION - R. Sh. Khaliullin; E. V. Leonteva (Вестник Кемеровского государственного университета, 2015)
The new method for determination of tetrafluoroborate by potentiometric titration is presented. The method is based on the hydrolysis of the tetrafluoroborate anion in water solutions and it takes into account the appropriate correction factor. The perchlorate ion is usually dependent to the tetrafluoroborate quantitive determination, then tetrafluoroborate and perchlorate exist in one solution. The discussed method resolves this analytical problem.